FIRST MAGNESIOFERRITE FIND IN KAMCHATKA - Anan'yev V.V.; Vergasova L.P. (My University, 1987)
Magnesioferrite is the magnesian end member of the large ferrispinel group with the general formula MeFe2O4. We detected magnesioferrite in olivine-anorthite nodules from a continuously differentiated lava flow of the Malyy Semyachik volcano and among products of the Great Tolbachik fissure eruption (GTFE), Kamchatka, 1975 to 1976. The rocks where we detected magnesioferrite, namely, olivine-anorthite nodules and basalt, exhibit evidence of heat-induced stress and chemical corrosion, expressed in the recrystallization of olivine with an increase in its magnesium content from 82 to 87 percent Fo in nodules and from 88 to 97 percent Fo in basalt.